2011
DOI: 10.1111/j.1744-7909.2011.01047.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Ecological Effects of Transgenic Bacillus thuringiensis Crops on Non‐Target OrganismsF

Abstract: The application of recombinant DNA technology has resulted in many insect-resistant varieties by genetic engineering (GE). Crops expressing Cry toxins derived from Bacillus thuringiensis (Bt) have been planted worldwide, and are an effective tool for pest control. However, one ecological concern regarding the potential effects of insect-resistant GE plants on non-target organisms (NTOs) has been continually debated. In the present study, we briefly summarize the data regarding the development and commercial us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 160 publications
(198 reference statements)
3
63
0
1
Order By: Relevance
“…Currently, available transgenic plants resistant to caterpillars contain genes of the bacterium Bacillus thuringiensis (Bt) that encode lethal toxins for certain insect groups. Bt plants have the potential to minimize losses caused by insect pests, especially the order Lepidoptera, as well as reduce insecticide use (Yu et al, 2011). Bt insecticidal proteins kill insects by a process comprising the following steps: crystal solubilization processing, conversion to an active protoxin form, high-affinity binding to the midgut receptors, irreversible insertion of the toxin into the membrane, and the formation of infection pores (Bravo et al, 2005;de Maagd et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, available transgenic plants resistant to caterpillars contain genes of the bacterium Bacillus thuringiensis (Bt) that encode lethal toxins for certain insect groups. Bt plants have the potential to minimize losses caused by insect pests, especially the order Lepidoptera, as well as reduce insecticide use (Yu et al, 2011). Bt insecticidal proteins kill insects by a process comprising the following steps: crystal solubilization processing, conversion to an active protoxin form, high-affinity binding to the midgut receptors, irreversible insertion of the toxin into the membrane, and the formation of infection pores (Bravo et al, 2005;de Maagd et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the fact that they are different genotypes, this is still indicative of the action of Cry1Ac protein on H. armigera. This protein causes a reduction in feeding and, consequently, starvation of larvae by specific binding in the ciliated membranes of the midgut, leading to death (Yu et al, 2011).…”
Section: Seed Treatment In Cry1ac Soybeanmentioning
confidence: 99%
“…15 In addition to the arguments on the fate of Bt proteins, debates are going on for their ecological risks. 5,16 Although no conclusive decision has been drawn until now, previous studies showed that the residual Bt proteins might adversely affect soil biodiversity due to their toxicity to the invertebrates and microorganisms. 17 Therefore, more studies are needed to understand the fate and risks of soil-associated Bt proteins, and an effective and robust method for analyzing trace amounts of Cry proteins in soil is the premise of these types of research.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,3 The widespread planting of Bt crops has raised concerns on their environmental risks. 4,5 Insecticidal Cry proteins produced by Bt crops may be released to soil through roots exudates, tasseling, or plant residues. As a consequence, persistence of Cry proteins in soil become an urgent concern.…”
Section: ■ Introductionmentioning
confidence: 99%